Induced pluripotent stem cell-derived human macrophages as an infection model for Leishmania donovani. - Lore Baert; Serena Rudy; Mélanie Pellisson; Thierry Doll; Romina Rocchetti; Marcel Kaiser; Pascal Mäser; Matthias Müller (Public Library of Science (PLoS), 2024)
The parasite Leishmania donovani is one of the species causing visceral leishmaniasis in humans, a deadly infection claiming up to 40,000 lives each year. The current drugs for leishmaniasis treatment have severe drawbacks and there is an urgent need to find new anti-leishmanial compounds. However, the search for drug candidates is complicated by the intracellular lifestyle of Leishmania. Here, we investigate the use of human induced pluripotent stem cell (iPS)-derived macrophages (iMACs) as host cells for L. donovani. iMACs obtained through embryoid body differentiation were infected with L. donovani promastigotes, and high-content imaging techniques were used to optimize the iMACs seeding density and multiplicity of infection, allowing us to reach infection rates up to 70% five days after infection. IC50 values obtained for miltefosine and amphotericin B using the infected iMACs or mouse peritoneal macrophages as host cells were comparable and in agreement with the literature, showing the potential of iMACs as an infection model for drug screening.